Evidence of Arctic sea ice thinning from direct observations. Issue 14 (23rd July 2014) - Renner, Angelika H. H.; Gerland, Sebastian; Haas, Christian; Spreen, Gunnar; Beckers, Justin F.; Hansen, Edmond; Nicolaus, Marcel; Goodwin, Harvey
Abstract The Arctic sea ice cover is rapidly shrinking, but a direct, longer‐term assessment of the ice thinning remains challenging. A new time series constructed from in situ measurements of sea ice thickness at the end of the melt season in Fram Strait shows a thinning by over 50% during 2003–2012. The modal and mean ice thickness along 79°N decreased at a rate of 0.3 and 0.2 m yr−1, respectively, with long‐term averages of 2.5 and 3 m. Airborne observations reveal an east‐west thickness gradient across the strait in spring but not in summer due to advection from more different source regions. There is no clear relationship between interannual ice thickness variability and the source regions of the ice. The observed thinning is therefore likely a result of Arctic‐wide reduction in ice thickness with a potential shift in exported ice types playing a minor role.